2022
DOI: 10.3390/jcm11041062
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Guided Tissue Regeneration Techniques on the Success Rate of Healing of Surgical Endodontic Treatment: A Systematic Review and Network Meta-Analysis

Abstract: Several regeneration techniques and materials have been proposed for the healing of bone defects after surgical endodontic treatment; however, the existing literature does not provide evidence on the most recommended techniques or materials. The aim of the present systematic review and network meta-analysis (NMA) is to summarize the clinical evidence on the efficacy of guided tissue regeneration techniques (GRTs). The PRISMA recommendations were followed. Four databases were searched up to December 2021. Rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…GTR in endodontic surgeries has been a promising technique to enhance the ideal regeneration after endodontic surgeries and enhance the overall clinical outcome, especially in cases with cortical defects or cases with a periodontal component, such as deep probings on the tooth or a connection between concomitant periodontal and endodontic defects (Setzer & Kratchman, 2022. ; Zubizarreta‐Macho et al., 2022)Since the current study's criteria included lesions from isolated endodontic disease as well as cases with cortical defects or cases that have combined periodontal involvement, the authors decided on GTR approach.…”
Section: Discussionmentioning
confidence: 99%
“…GTR in endodontic surgeries has been a promising technique to enhance the ideal regeneration after endodontic surgeries and enhance the overall clinical outcome, especially in cases with cortical defects or cases with a periodontal component, such as deep probings on the tooth or a connection between concomitant periodontal and endodontic defects (Setzer & Kratchman, 2022. ; Zubizarreta‐Macho et al., 2022)Since the current study's criteria included lesions from isolated endodontic disease as well as cases with cortical defects or cases that have combined periodontal involvement, the authors decided on GTR approach.…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review of the literature (Tsesis et al, 2011) reported that GTR techniques could improve bone regeneration following surgical endodontic treatment particularly in cases with large and throughand-through periapical lesions (Tsesis et al, 2011). Other, more recent, both narrative and systematic reviews of the literature confirmed that GTR procedure could promote bone healing after surgical endodontic treatment, confirming that their efficacy is higher in presence of large periapical lesions (Corbella et al, 2016;Zubizarreta-Macho et al, 2022). However, those reviews did not performed a specific analysis on endodontic-periodontal lesions, leaving the prognosis of such cases unknown, and not systematically explored in literature.…”
Section: Introductionmentioning
confidence: 93%
“…These findings concurred with the meta-analysis by Deng et al (2016), who confirmed the increased effectiveness of combinations of membranes and bone replacement analogues. However, the same study also concluded that the singular use of bone replacement materials improved the surgical outcome for endodontic surgery, which was not confirmed by a recent network meta-analysis for bone graft materials alone (Zubizarreta-Macho et al, 2022). Zubizarreta-Macho et al (2022) appraised the clinical evidence on the efficacy of GTR techniques and included 11 randomized clinical trials comparing six GRT techniques, including bone graft, membrane, membrane plus bone graft, platelet-rich plasma or membrane plus platelet-rich plasma.…”
Section: Guided Tissue Regeneration (Gtr)mentioning
confidence: 99%
“…However, the same study also concluded that the singular use of bone replacement materials improved the surgical outcome for endodontic surgery, which was not confirmed by a recent network meta-analysis for bone graft materials alone (Zubizarreta-Macho et al, 2022). Zubizarreta-Macho et al (2022) appraised the clinical evidence on the efficacy of GTR techniques and included 11 randomized clinical trials comparing six GRT techniques, including bone graft, membrane, membrane plus bone graft, platelet-rich plasma or membrane plus platelet-rich plasma. Both the membrane and the membrane plus bone graft techniques demonstrated statistically significant odds ratios compared to procedures conducted without GTR.…”
Section: Guided Tissue Regeneration (Gtr)mentioning
confidence: 99%
See 1 more Smart Citation